2014
DOI: 10.1002/2014jd021744
|View full text |Cite
|
Sign up to set email alerts
|

Properties of light‐absorbing aerosols in the Nagoya urban area, Japan, in August 2011 and January 2012: Contributions of brown carbon and lensing effect

Abstract: The optical properties of aerosols at 405 and 781 nm were measured in an urban site in Nagoya,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 79 publications
4
45
1
Order By: Relevance
“…The diurnal variations of the HGFs of the nearly hydrophobic and more hygroscopic particles were not clear, which was in contrast to a large decrease in the HGF of the more hygroscopic particles from morning to noon in Tokyo in the summer [ Mochida et al , ] and a large increase in the HGF of the nearly hydrophobic particles in Mexico City in the spring [ Wang et al , ]. Figures a–c present the time series of the mass concentrations of the chemical components in the submicrometer particles (data in Figures a–c are from Nakayama et al []). Organics, sulfate, and ammonium were the major components among those detected in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diurnal variations of the HGFs of the nearly hydrophobic and more hygroscopic particles were not clear, which was in contrast to a large decrease in the HGF of the more hygroscopic particles from morning to noon in Tokyo in the summer [ Mochida et al , ] and a large increase in the HGF of the nearly hydrophobic particles in Mexico City in the spring [ Wang et al , ]. Figures a–c present the time series of the mass concentrations of the chemical components in the submicrometer particles (data in Figures a–c are from Nakayama et al []). Organics, sulfate, and ammonium were the major components among those detected in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The number size distributions (d N CN /dlog d dry ) of the aerosol particles under dehumidified conditions (RH: 26% ± 4% (mean ± SD)) were measured in the range of d dry from 17.5 to 982 nm with a time resolution of 5 min. The mass concentrations of OC and EC after passing through another cyclone (URG, URG‐2000‐30EHB; cutpoint: 1 µm) were measured using a semicontinuous EC/OC analyzer (Sunset Lab., model 4) with a time resolution of 1.5 h [ Nakayama et al , ]. The mass concentrations of EC and OC were not used when the mass concentrations were smaller than the sum of the mean concentrations of the blank filter period and 3 times their SD.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A recent chamber study coupling actual ambient air with seed BC particles implies that the timescale for E abs reaching 2.4 is only 5 h in Beijing but 18 h in Houston . Field studies conducted in recent years have also substantiated enhanced light absorption in Canada (Knox et al, 2009;Chan et al, 2011), USA (Lack et al, 2012b), UK (Liu et al, 2015) and Japan (Nakayama et al, 2014;Ueda et al, 2016). In contrast, field studies in California, USA , found a weaker light absorption enhancement (6 % on average).…”
Section: Introductionmentioning
confidence: 96%
“…BrC is typically quoted as having AAE values ranging from 1.5 to ≈ 7.0. 24,31,3845 Additional experimental studies are required to fully understand the impact of BC embedded within BrC.…”
Section: Introductionmentioning
confidence: 99%